Technological Change in Uganda’s Agriculture between 2005-2010 - Kalibwani, R.M.; Mutenyo, J.; Kato, E. (RUFORUM., 2014)
The study estimates the rate of technological change in Uganda’s agriculture between 2005- 2010 across the 4 major regions of the country. Using a nationally representative household panel data set, we use a time trend variable in the stochastic production frontier to account for hicks-neutral technological change, then the frontier is re-modeled using binary time trend dummy variables to capture the temporal pattern of technological change. Overall we find that technological progress was small and insignificant of 0.031% but further decomposition at regional level revealed more interesting findings. The western region had technological progress at 0.6%, and the central region had technological regress of 0.57%, both significant at the 5% level. The northern region had technological progress at 0.008% and the eastern region had technological regress of 0.11% both insignificant at 5% level. The findings suggest that more public and private investments in region-specific technology development would be required to accelerate technological progress especially in the northern and eastern regions of the country. Alternatively with the existing level of investment, effort should be made to address the institutional issues that constrain efficient dissemination of the technologies developed from the NARS.
Keywords: Hicks-neutral technological change; Technological progress/regress; Stochastic production frontier